Analysis of Amino Acid Sequence of SARS-CoV, SARS-CoV-2, and MERS-CoV Spike Glycoproteins: Preliminary Study for Obtaining Universal Peptide Vaccine Candidates - Yani Suryani; Opik Taupiqurrohman (Biogenesis: Jurnal Ilmiah Biologi, 2020)
In the manufacture of universal peptide vaccines, it is necessary to analyze the amino acids of the various candidates. Therefore, this study aims to examine the amino acids of the spike glycoproteins of SARS-CoV, SARS-CoV-2, and MERS CoV. The method used is the alignment of the amino acid spike glycoprotein between SARS-CoV with SARS-CoV-2, MERS CoV with SARS-CoV-2, and SARS-CoV with MERS-CoV using web-based software water emboss. The analysis result showed that SARS and SARS CoV-2 were very similar with 87% similarity and 76.4% identity values. In contrast, SARS CoV-2 with MERS and SARS with MERS were very different, having similarity and identity values less than 70%. Therefore, it is reasonable to conclude that spike glycoprotein's peptide is only useful from attacks by the SARS-CoV and SARS-CoV-2 viruses.